Досвід європейських країн у впровадженні екологічних інновацій в готельному бізнесі - Балджи, М. Д.; Балджи, Марина Дмитрівна; Яслинська, К. Д. (My University, 2022)
Стаття присвячена вивченню досвіду розвитку екологічного готельного бізнесу європейських країн для можливостей його використання в Україні. Формування концепції впровадження екологічного готелю спрямовано на якісну систему комфортного життя в гармонії з довкіллям та дозволяє окреслити особливості функціонування екологічного готелю. Останні включають: систему збереження ресурсів; використання альтернативних джерел енергії; мінімізації хімічних реагентів, що використовуються; застосування бактерицидних методів, що розкладають бруд та відходи; зменшення чи унеможливлення використання алергенів; якісна утилізація відходів та сміття; застосування повністю замкнутих систем для регенерації води і повітря; організація харчування з залученням сертифікованих продуктів та очищеної води. Суттєвим для екоготелів виступає дизайн, який базується на використанні «природних» кольорів та матеріалів вторинної переробки. Унікальним підходом є дотримання філософії відмови від електронних пристроів. Проаналізована міжнародна програма добровільної екологічної сертифікації підприємств готельного бізнесу «Green Key» та діяльність асоціації BIO HOTELS, досвід яких доречно використовувати в готельно-ресторанному бізнесі України. Розглянуто створення асоціацій підприємств готельної сфери та можливість створення таких об’єднань в Україні.

The article is devoted to the study of the experience to develop the ecological hotel business in European countries on the possibilities of its use in Ukraine. The formation of ecological hotels concept is aimed at a quality system of comfortable living in harmony with the environment and allows to outline the features of the ecological hotel. These features include: a system for saving resources; use of alternative energy sources; minimization of chemical reagents used; application of bactericidal methods that decompose dirt and waste; reducing or preventing the use of allergens; high-quality utilization of waste and garbage; use of completely closed systems for water and air regeneration; catering with certified products and purified water. The interior design of ecological hotels, which is based on the use of «natural» colors and recycled materials, is no exception for eco-hotels. A unique approach is to adhere to the philosophy of abandonment of electronic devices. The availability of eco-labels in ecological hotels increases its attractiveness to potential customers, and the use of ecological certification includes the coverage area and objects of certification. The international program of voluntary environmental certification of hotel business enterprises «Green Key» and the activities of the association BIO HOTELS, whose experience is appropriate to use in the hotel and restaurant business of Ukraine, are analyzed. The advantages of the latter are determined: construction biology and use of natural building materials; regionality and seasonality of organic products; availability of certified organic and natural cosmetics and hygiene products only; complete waste recycling; exclusion of plastic use; environmental electri-city; availability of electronic charging stations for electric vehicles. To support environmentally sound operation, the independent experts carry out the inspection and draw up a climate balance sheet, in which the company's own CO2 emissions are recorded. The association aims to define its climate-positive activities, combined with common goals and ideas. Promoting the idea of environmentally friendly organic origin and living in accordance with this goal distinguishes BIO HOTELS among other associations that exist in Europe. The environmental field covers all spheres of life and business in Europe, and trends in this development are rapidly supported by Ukrainian hospitality enterprises. The creation of hotel enterprises' associations and the possibility of creating such associations in Ukraine are considered.
Балджи М. Д. Досвід європейських країн у впровадженні екологічних інновацій в готельному бізнесі / М. Д. Балджи, К. Д. Яслинська // Розвиток методів управління та господарювання на транспорті : Зб. наук. праць. – 2022. – №. 2(79). – 79-88. DOI: 10.31375/2226-1915-2022-2-79-88
Keywords: екологічний готельний бізнес; екологічні готелі; еко-маркування; екологічна сертифікація; кліматичний баланс; асоціація готельних підприємств; ecological hotel business; ecological hotels; eco-labeling; ecological certification; climate balance; association of hotel enterprises; Research Subject Categories::SOCIAL SCIENCES